Gender equality and the gender gap in life expectancy in the European Union. Issue 2 (14th February 2022) - Pinho-Gomes, Ana-Catarina; Vassallo, Amy; Carcel, Cheryl; Peters, Sanne; Woodward, Mark
Abstract : Introduction: Life expectancy (LE) depends on the wider determinants of health, which have different impact in women and men. Therefore, this study aimed to investigate whether gender equality was correlated with LE in women and men. Methods: Gender equality in the 27 European Union (EU) member states between 2010 and 2019 was estimated using a modified Gender Equality Index (mGEI), based on the index developed by the European Institute for Gender Equality. The correlation between this mGEI and LE and the gender gap in LE was calculated using the Spearman correlation coefficient. Results: Between 2010 and 2019, LE increased more for men than women, which resulted in a narrowing of the gender gap in LE in the EU. During the same period, there was an increase in gender equality, as measured by the mGEI, although with substantial heterogeneity between countries. There was a strong correlation between the mGEI and the gender gap in LE (−0.880), which was explained by a stronger correlation between the mGEI and longer LE in men than in women (0.655 vs 0.629, respectively). The domains of the mGEI most strongly associated with a narrowing of the gender gap in LE were health, money and knowledge, while power was the domain with the weakest association. Conclusions: Gender equality appears to be at least as beneficial to men as women with regard to LE, thus reinforcing the key role gender equality plays in improving population health and longevity.